Multi-path routing scheme for 6LoWPAN wireless sensor network. (1st January 2013) - Xiaonan, Wang; Haili, Huang; Yuan, Yang; Xiaoqing, Pan
This paper proposes a multi-path routing scheme for 6LoWPAN wireless sensor networks. This scheme is performed in the link layer, so intermediate sensor nodes can route a data frame without processing the headers in the upper layers. As a result, the routing cost is reduced and the routing efficiency is improved. In this scheme, a source node can establish multiple disjoint routing paths during one routing discovery process. When one routing path fails, another routing path can continue working without routing discovery process. This scheme also presents the routing path repair algorithm. If an intermediate node detects that the next hop is unreachable, then it repairs the corresponding routing path to ensure that the data are correctly routed to the destination node. The performance parameters of this scheme are evaluated. The simulation results show that this scheme can reduce the routing cost and shorten the routing delay effectively.